Tools of single party hegemony in Tanzania: evidence from surveys and survey experiments. Issue 2 (23rd February 2017) - Croke, Kevin
ABSTRACT: Political systems dominated by a single party are common in the developing world, including in countries that hold regular elections. Yet we lack knowledge about the strategies by which these regimes maintain political dominance. This article presents evidence from Tanzania, a paradigmatic dominant party regime, to demonstrate how party institutions are used instrumentally to ensure the regime's sustained control. First, I show that the ruling party maintains a large infrastructure of neighbourhood representatives, and that in the presence of these agents, citizens self-censor about their political views. Second, I provide estimates of the frequency with which politicians give goods to voters around elections, demonstrating that such gifts are more common in Tanzania than previous surveys suggest. Third, I use a survey experiment to test respondents' reaction to information about corruption. Few voters change their preferences upon receipt of this information. Taken together, this article provides a detailed picture of ruling party activities at the micro-level in Tanzania. Citizens conceal opposition sympathies from ten cell leaders, either because they fear punishment or seek benefits. These party agents can monitor citizens' political views, facilitating clientelist exchange. Finally, citizens' relative insensitivity to clientelism helps explain why politicians are not punished for these strategies.